Making health and wellbeing: Sport and women's care in rural Canada. (January 2019) - Mair, Heather; Leipert, Beverly D.; Scruby, Lynn S.; Meagher-Stewart, Donna
Highlights: Rural women use sport as a way to shape their health and wellbeing. Motivations for sport participation can be seen as response to access to health services in rural areas. Sport clubs in rural areas can be vital resources for community health and wellbeing. Participants' membership in rural sport (curling) clubs are influenced by broader material conditions.